Correlação entre torque, equlíbrio e função do joelho após reconstrução do LCA - Noronha Neta, Maria Isabel de (2009)
Background: Several studies emphasize the importance of assessing the knee function after anterior cruciate ligament (ACL) reconstruction. The influence of several variables on the function of these patients has been analyzed, but there is no consensus in the science literature. Purpose: To evaluate the correlation between the torque and balance on the knee function after ACL reconstruction. Methods: 23 males patients with ACL reconstruction were tested. The procedures of the study included analysis of concentric peak torque at 60o/s and 180o/s of quadriceps femoris and hamstring muscle with a isokinetic dynamometer. The balance in single-limb stance was measured with stabilometry. The functional performance were performed by two hop tests. To estimate the subjective function of the patients was applied Lysholm Knee Scoring Scale and a Global Rating scale. Results: The analysis of data showed a moderate positive correlation between knee extensor torque and functional performance tests (r= 0,48; p=0,02). A moderate negative correlation was found between the two variables of the stabilometry center of pressure and average speed of centre of pressure and the Global Rating scale (r = -0.4, p = 0,04 and r = -0,49, p = 0 ,02, respectively). No correlation was found between peak torque and balance in single-limb stance. Conclusion: The results of the present study suggest that knee extensor strength and postural balance have some influence on knee function in patients after ACL reconstruction